Structural, capacitive and resistive characteristics of (Pb0.6Bi0.2Sm0.2)(Fe0.4Ti0.6)O3. Issue 10 (15th May 2022) - Samal, S.K.; Biswal, B.; Mallick, M.K.; Choudhary, R.N.P.; Bhuyan, S.
Abstract: Samarium substituted BiFeO3 –PbTiO3 ceramic compound of (Pb0.6 Sm0.2 Bi0.2 )(Fe0.4 Ti0.6 )O3 has been fabricated by mixed oxide solid state reaction method. The crystallographic structure from XRD study, distribution of grains from SEM micrograph, dielectric behavior, conductivity spectrum, impedance along with electric modulus spectroscopy have been illustrated. The experimental results corroborate the impact of samarium substitution in BiFeO3 –PbTiO3 entailing reduced grain size, higher dielectric response with reasonably dielectric loss and enrichment in capacitive behavior with negative temperature coefficient of resistance. The temperature dependent conductivity spectra exhibit Arrhenius behavior, whereas the frequency dependent conductivity spectra follow the Jonscher universal power law. The basic correlated barrier hopping (CBH) model governs the charge transport mechanism in the fabricated compound. The exploration reveals the enriched dielectric and electrical behavior that endorse the samarium substituted material as a potential ceramic entity for designing electronic devices such as capacitors and ferroelectric accessories.